Comparing telehealth to traditional office visits for patient management in the COVID-19 pandemic: A cross-sectional study in a respiratory assessment clinic. (June 2023) - Phillips, J Cole; Lord, Richard W; Davis, Stephen W; Burton, Amanda A; Kirk, Julienne K
Introduction: The aim of this study was to examine whether telehealth is as safe and effective as traditional office visits in assessing and treating patients with symptoms consistent with COVID-19. Methods: In this retrospective cross-sectional study, the primary outcome was any 14-day related healthcare follow-up event(s). Secondary outcomes were the type of 14-day related follow-up event including hospital admission, emergency department visit, office visit, telehealth visit and/or multiple follow-up visits. Individual visit types were identified due to the significant difference between a hospital admission and an office visit. Logistic regressions were done using the predictors of visit type, age, gender and comorbidities and the primary outcome variable of a related follow-up visit and then by follow-up type: hospital admission, emergency department visit or office visit. Results: Of 1305 visits, median age was 42.3 years and 65.8% were female. Traditional office visits accounted for 741 (56.8%) of initial visits, while 564 (43.2%) visits occurred via telehealth. One hundred and forty-six (25.9%) of the telehealth visits resulted in a 14-day related healthcare follow-up visit versus 161 (21.7%) of the office visits (adjusted odds ratio (OR) 1.22, 95% CI 0.94–1.58). Discussion: There was no significant difference in related follow-ups of initial telehealth visits compared to initial office visits including no significant difference in hospital admission or emergency department visits. These findings suggest that based on follow up healthcare utilization, telehealth may be a safe and effective option in assessing and treating patients with respiratory symptoms as the COVID-19 pandemic continues.